2011
DOI: 10.1021/cg101561s
|View full text |Cite
|
Sign up to set email alerts
|

Morpholine-4-Carbodithioate Se and Te Complex as Single Source Precursor for Synthesis of Se and Te with Diverse Morphologies

Abstract: The morphological control, physical and chemical properties of semiconducting micro/nanomaterals is strongly influenced by their dimensionality. As a result, one-dimensional (1D) nanosized Se and Te nanostructures, such as nanotubes, 1À4 nanorods, 5,6 nanowires, 7,8 nanobelts, 9,10 and nanoribbons, 11,12 have gained a considerable amount of attention in the past several decades due to their unique properties. Selenium is a nontoxic semiconductor having a bandgap of 1.7 eV and finds applications in photocells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 55 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…The crystalline phase confirmation of the designed materials was carried out by X-ray diffraction study. Figure 2c (Sahoo and Srivastava 2011;Zhang et al 2018;Jiang et al 2017). The lattice parameters (a = 0.75 nm, c = 0.436 nm) as calculated from the resulted diffraction pattern are well matching with the corresponding calculations The XRD results reveal that the composite is successfully synthesized and no other impurities peaks were observed.…”
Section: Structural Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…The crystalline phase confirmation of the designed materials was carried out by X-ray diffraction study. Figure 2c (Sahoo and Srivastava 2011;Zhang et al 2018;Jiang et al 2017). The lattice parameters (a = 0.75 nm, c = 0.436 nm) as calculated from the resulted diffraction pattern are well matching with the corresponding calculations The XRD results reveal that the composite is successfully synthesized and no other impurities peaks were observed.…”
Section: Structural Analysismentioning
confidence: 98%
“…Temperature and addition of hydrazine have a substantial effect on the aspect ratio of nanorods, and the present study also reveals that higher temperature affects the size of the growing nanorods. At room temperature, the material agglomerates while at a higher temperature, the agglomeration and particles size decreases (Jafari et al 2013;Sahoo and Srivastava 2011). The rate of nucleation and particles growth increases with increasing temperature, which affects the aspect ratio.…”
Section: Sem Analysismentioning
confidence: 99%
“…7a shows that the presence of two peaks at about 115.4 and 134.3 cm À1 is observed at room temperature, which are close to those reported previously. 25 Interestingly, no shi in peak positions is observed for the tellurium nanorods. While for the polycrystalline nanoplates, a new peak at 262.8 cm À1 is observed except the two 115.4 and 134.3 cm À1 peaks under the same experimental condition.…”
Section: Possible Formation Mechanism Of Tellurium Nanoplatesmentioning
confidence: 99%
“…The synthesis of nanosized materials has received great interest because of their unique properties, which differ largely from those of the bulk materials. [4][5][6][7] Owing to the interesting physical properties of selenium, as well as the quantum-size effect, nano-selenium was also being considered as an excellent material, which could be used for producing novel devices with new types of applications or greatly enhancing the performance of existing devices. 8,9 On the other hand, some recent studies showed that supra-nutritional levels of selenium nanoparticles (SeNPs) had no obvious toxic effects and they were considered as promising therapeutic materials.…”
Section: Introductionmentioning
confidence: 99%